Design and fabrication of a 3.3 kV 4H-SiC MOSFET - 黄润华 陶永洪 柏松 陈刚 汪玲 刘奥 卫能 李赟 赵志飞 (Journal of semiconductors, 2015)
A 4H-SiC MOSFET with breakdown voltage higher than 3300 V has been successfully designed and fabricated. Numerical simulations have been performed to optimize the parameters of the drift layer and DMOSFET cell structure of active area. The n-type epilayer is 33μm thick with a doping of 2.5 × 10^15 cm-3. The devices were fabricated with a floating guard ring edge termination. The drain current 1d= 5 A at Vg = 20 V, corresponding to vd = 2.5 v.